The implementation of blended learning in the new normal era at vocational school of health - Resmiaty, Tetty; Chaeruman, Uwes Anis; Kusumawardani, Dwi (Jurnal Pendidikan Vokasi, 2021)
This study aims to describe blended learning in the new normal era in vocational health schools. Vocational education contributes to preparing skilled workforce graduates. Therefore, vocational education must prepare the learning process based on the conditions and needs of students. The research method used was a qualitative approach. A case study was conducted to empirically investigate the phenomenon of the learning process in the new normal era through blended learning. This study collaborated with 96 fourth-semester and 92 sixth-semester students at the Medical Laboratory Technology Study Program in Associate Degree of Health Polytechnic Ministry of Health Manado. The study results showed that during Covid-19, students could not practice directly in the laboratory freely, so it took much work to apply the required course applications in the form of practice. Although out of 188 students, only 110 students often use smartphones in the blended learning process. Students experience the most serious difficulty in understanding and practicing laboratory quality control courses, with a percentage of 38.6%. Therefore, laboratory quality control is considered in terms of student responses to difficult subjects to understand during the online learning process. So that further research is needed to develop a learning system that can increase student learning motivation. Not only up to motivation but students also have to understand how to use technology well.